Improving of the methodology for analyzing of insect nematodiasis - Kovtun , A. (Quarantine and plant protection, 2025)
Goal. To improve the methodological approach to the helminthological analysis of insects as an essential component of insect infectious pathologies, using the parasitic system «insect host Galleria mellonella — nematodes Rhabditida» as a case study. Methods. The methodological basis of the study comprises data from long-term original research on entomopathogenic nematodes (Nematoda: Rhabditida: Steinernematidae, Heterorhabditidae) in agroecosystems of Ukraine (conducted between 2016 and 2024), as well as current scientific literature by Ukrainian and international scholars on insect helminthodiagnostic methods. The study employed both general scientific and specialized research methods, including theoretical analysis, fieldwork, laboratory experiments, and mathematical-statistical techniques. Results. A scientific and methodological approach to helminthological analysis of insects (exemplified by Galleria mellonella L., 1758) within the context of insect infectious pathologies has been improved. This approach is based on the use of an original «entomohelminthological formula» for the assessment of the species composition and condition of helminths (Nematoda: Rhabditida) following a complete helminthological dissection of insects. Conclusions. The use of complete helminthological dissections in combination with the original «entomohelminthological formula» enables not only quantitative detailing but also qualitative characterization of pathological changes in insects (Insecta) associated with helminthic (nematode) infections (Nematoda). The results of the research can be applied in entomological studies after the collection and identification of insects infected with nematode parasites (pathogens).